ENDORSE EFFECT ADE GOVINDA'S SELEBGRAM AND INSTAGRAM POST @ BM.ORIGINAL ACCOUNT FOR FOLLOWERS ' INTEREST IN BUYING SNEAKERS SHOES - Renaldo Aswansyah Putera; Nani Nurani Muksin; Aminah Swarnawati (Jurnal Multidisiplin Sahombu, 2022)
The purpose of the theme adopted from the title above is to find out the influence of Ade Govinda's celebrity Endorsements and @ BM.ORIGINAL's Instagram account posts on Followers regarding their interest in buying Sneakers. This research method uses a quantitative approach by distributing questionnaires to the 98 follower respondents mentioned above, then the results of the data are processed with the help of the SPSS 25 application. The population of this study is all Instagram social media users who follow the @ BM. Original account with the sample used random sampling. The results of the data processing carried out are that the Endorse Selebgram variable partially has an influence on buying interest, the results obtained are t-count > t-table and sig < 0.05 (2,800 > 1.985 and 0.016 < 0.05), the social media the Instagram variable partially has an influence on buying interest, the test results are t-count > t-table and sig < 0.05 (2.372 > 1.985 and 0.020 < 0.05), and the Endorse Selebgram variable and Instagram social media simultaneously have an influence on SPSS buying interest The results of the F test are F-count > F-table and sig < 0.05 (4.981 > 3.090 and 0.009 < 0.05